(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder characterized by recurrent upper airway obstruction during sleep, resulting in excessive daytime sleepiness, impaired quality of life, and increased cardiovascular morbidity. Nasal obstruction caused by structural abnormalities such as deviated nasal septum and turbinate hypertrophy may exacerbate OSA symptoms and negatively affect sleep quality. Functional nasal surgery has been proposed as an adjunctive treatment to improve nasal airflow and alleviate sleep-related symptoms. Objective: To evaluate the role of functional nasal surgery in improving sleep quality among patients with obstructive sleep apnea using the Epworth Sleepiness Scale (ESS). Methods: This prospective interventional study was conducted from January 2024 to June 2025 in a tertiary care teaching hospital. Ninety adult patients diagnosed with OSA and symptomatic nasal obstruction underwent functional nasal surgery. Preoperative and postoperative daytime sleepiness was assessed using the ESS. Surgical procedures included septoplasty, inferior turbinate reduction, septoplasty with turbinate reduction, and nasal valve correction. Patients were followed for three months postoperatively. Statistical analysis was performed using SPSS version 26.0, with p < 0.05 considered statistically significant. Results: The majority of participants were male (67.8%) and overweight or obese (82.2%). Deviated nasal septum was the most common nasal pathology (52.2%). Mean ESS scores significantly decreased from 13.84 ± 3.21 preoperatively to 8.21 ± 2.74 postoperatively (p < 0.001). The proportion of patients with normal ESS scores increased from 20.0% to 75.6%, while moderate and severe daytime sleepiness decreased substantially after surgery. Patients with normal body mass index demonstrated greater postoperative improvement than obese individuals (p = 0.032). Conclusion: Functional nasal surgery significantly improved daytime sleepiness and subjective sleep quality in patients with OSA and nasal obstruction. These findings support its role as an effective adjunctive intervention in the multidisciplinary management of obstructive sleep apnea.